2009
DOI: 10.4085/1062-6050-44.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Joint Laxity Associated With Increased Medial Foot Loading in Female Athletes

Abstract: Context:The relationship between generalized joint laxity and plantar pressure distribution of the foot and the potential implications for lower extremity injury have not been studied.Objective: To determine the relationship between generalized joint laxity and dynamic plantar pressure distribution. We hypothesized that individuals with greater generalized joint laxity, or hypermobility, would have greater dynamic medial midfoot pressure and loading during walking than nonhypermobile individuals.Design: Case c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…28 Although pedobarographic analysis in our study measured static plantar pressure, it had a number of similarities with Foss and colleagues' findings, in which dynamic plantar pressure was measured. 17 In the group with high generalized joint laxity peak pressure and maximum force were greater in comparison with low generalized joint laxity group. 17 These results were correlated with our study, where peak pressure on the non-dominant side was greater in the group with high BHJMI scores (p= 0.01).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…28 Although pedobarographic analysis in our study measured static plantar pressure, it had a number of similarities with Foss and colleagues' findings, in which dynamic plantar pressure was measured. 17 In the group with high generalized joint laxity peak pressure and maximum force were greater in comparison with low generalized joint laxity group. 17 These results were correlated with our study, where peak pressure on the non-dominant side was greater in the group with high BHJMI scores (p= 0.01).…”
Section: Discussionmentioning
confidence: 84%
“…17 In the group with high generalized joint laxity peak pressure and maximum force were greater in comparison with low generalized joint laxity group. 17 These results were correlated with our study, where peak pressure on the non-dominant side was greater in the group with high BHJMI scores (p= 0.01).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Also, it was suggested that injured athletes with generalized joint hypermobility might require more time to rehabilitate before returning to sports to avoid reinjury. 11 Foss et al 16 investigated whether generalized joint laxity was correlated with dynamic plantar pressure in female soccer players and found that athletes with high generalized joint laxity demonstrated increased midfoot loading resulting from medial foot collapse, suggesting that those athletes might be at a greater risk of lower leg injuries. Similarly, a systematic review conducted by Pacey et al 29 indicated that athletes with generalized joint laxity might be at an increased risk of knee injuries during contact activities.…”
Section: Discussionmentioning
confidence: 99%